SASTRA DALAM ERA GLOBALISASI - Nancy Angelia Purba (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
The era of globalization has had a positive and negative impact on the lives of special nations in Indonesian literature. Indonesian literature must be able to position itself among other world literature which is more dominant, both in terms of quantity and quality. To be able to realize this, it is necessary to highlight the distinctive or ethnic nature of Indonesian literature. This is not easy to do because the influence of western culture is increasingly strong in various fields, especially in social, cultural and technological interactions. The global era is marked by the acceleration of the development of increasingly sophisticated science and technology, so that as if the world is a global village without a clear boundary and boundaries. Literature in globalization is also characterized by the inclusion of slang in literary works that are free from the language's features. The progress of science and technology makes literature recognized by outsiders. The global era has also provided opportunities for the world and humans who live in it to interact and communicate from different ends of the world, without obstacles space and time.